Saigami. Volume 2, The initiation exam - Seny (Saturday AM, 2023)
"The Initiation Exam throws an unexpected curveball at young Saigami candidates, including Ayumi, who has arrived in this strange fantasy world under mysterious circumstances. While these young, powerful teenagers have no way of knowing, the contest strings are being pulled from the shadows, putting their future careers--and their lives--in jeopardy. Ayumi and the others will have to act fast, be clever, and rely on unlikely alliances to survive this test. Can a fellow female Saigami initiate help Ayumi in her darkest hour? Refusing to be a damsel in distress, Ayumi's not ready to go down without a fight, and her mighty new flame powers are burning hotter than ever!" --